AMOUNTS OF VITAMIN A, VITAMIN E, VITAMIN C, ?-CAROTENE, LYCOPENE, GHRELIN, GLUTATHIONE, AND MDA IN FRUITS OF DIOSPYROS KAKI L. - Mukhtar, Zulaiha Gidado; Ibrahım, Muhammad Salihu; Ibrahım, Yusuf Ibrahim; Karatas, Fikret (My University, 2019)
In this study, the amounts of vitamins A, E, C, ?-carotene, lycopene, ghrelin, reduced and oxidized form ofglutathione (GSH, GSSG) with malondialdehyde (MDA) in ripe fruits of Diospyros kaki L. plant were determinedby using HPLC. The amount of vitamins A, E, C, ?-carotene, lycopene, ghrelin, GSH, GSSG and MDA inDiospyros kaki L. plant were found to be 0.40±0.06 – 0.92±0.08; 0.63±0.09 - 1.34±0.14; 47.00±0.80 - 65.61±1.56;2.08±0.18 - 3.36±0.30; 0.69±0.08 - 1.42±0.13; 2.14±0.65 - 7.98±1.06; 398.25±34.23 - 527.90±23.36; 23.67±8.89- 42.43±4.81 and 5.63±0.35 - 7.28±0.42 µg/g, respectively. It can be said that Diospyros kaki L. plant fruits are agood source of vitamin C, lycopene, ghrelin and glutathione. Findings suggest that the fruit of this plant may bea useful source of antioxidants. Differences in the amount of parameters in the Diospyros kaki L. fruit are thoughtto be due to the growth medium, climate, and environmental conditions.
Keywords: Biyoloji; Kimya; Analitik; Kimya; Tıbbi; Gıda Bilimi ve Teknolojisi; Veterinerlik